2015
DOI: 10.1542/peds.2014-3556
|View full text |Cite
|
Sign up to set email alerts
|

Late Preterm Birth and Neurocognitive Performance in Late Adulthood: A Birth Cohort Study

Abstract: OBJECTIVES: We studied if late preterm birth (34 weeks 0 days-36 weeks 6 days of gestation) is associated with performance on the Consortium to Establish a Registry for Alzheimer's Disease Neuropsychological Battery (CERAD-NB) in late adulthood and if maximum attained lifetime education moderated these associations.METHODS: Participants were 919 Finnish men and women born between 1934 and 1944, who participated in the Helsinki Birth Cohort Study. They underwent the CERAD-NB at a mean age of 68.1 years. Data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 62 publications
(67 reference statements)
2
58
0
1
Order By: Relevance
“…48 -51 There are also studies suggesting that these effects, including poorer cognitive outcomes, may persist into adolescence and adulthood. 52,53 The findings of this study add to the growing clinical and epidemiologic evidence that prolonging pregnancy (increasing gestational age), even at term (from 37-38 weeks), can benefit brain 6 To support informed decisionmaking with their pregnancy care provider, it is important for women and their families to have readily available and accessible information about the optimal duration of pregnancy and any increased risk of poorer development or other adverse outcomes associated with early planned birth. 55 This information is relevant given recent research reporting that >90% of women indicated the earliest gestational age for safe delivery was before 39 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…48 -51 There are also studies suggesting that these effects, including poorer cognitive outcomes, may persist into adolescence and adulthood. 52,53 The findings of this study add to the growing clinical and epidemiologic evidence that prolonging pregnancy (increasing gestational age), even at term (from 37-38 weeks), can benefit brain 6 To support informed decisionmaking with their pregnancy care provider, it is important for women and their families to have readily available and accessible information about the optimal duration of pregnancy and any increased risk of poorer development or other adverse outcomes associated with early planned birth. 55 This information is relevant given recent research reporting that >90% of women indicated the earliest gestational age for safe delivery was before 39 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…Epidemiologic studies show an association between late preterm birth and clinical adverse outcomes in childhood, adolescence, and adulthood 194200 . A recent report of an association between late preterm birth and impaired neurocognitive performance in late adulthood in a Finnish birth cohort underscores the potential importance of this mechanism of disease 201 . Therefore, further clinical and molecular phenotyping of maternal anti-fetal rejection is needed so that effective monitoring and management of pathological maternal anti-fetal rejection during pregnancy be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nearly 15 million infants worldwide who are born preterm (<37 weeks' gestation) each year (2), over 70% are born late-preterm (between 34+0 and 36+6 weeks+days' gestation) (3). The late-preterm infant is faced with a substantial risk of morbidity and mortality compared with term-born peers (4), including an increased risk of early growth faltering (5) and poorer long-term neurocognitive functioning (6) and socio-economic attainment (7). Yet, a large proportion of late-preterm individuals come to cope well, and the risk of mental disorders, for example, seems to be similar for late-preterm and term-born individuals (8).…”
Section: Introductionmentioning
confidence: 99%